2009
DOI: 10.1107/s1600536809054129
|View full text |Cite
|
Sign up to set email alerts
|

2-{[(4-Methoxyphenyl)dimethylsilyl]methyl}isoindoline-1,3-dione

Abstract: In the course of our studies of silicon-containing anti­cancer compounds, the title compound, C18H19NO3Si, was synthesized. The mol­ecular geometry including bond distances and angles involving the Si atoms are typical. Torsion angles associated with the isoindoline ring and the silyl group [C—N—Cmethyl­ene—Si = 90.5 (2) and −93.1 (2)°] indicate that there is no inter­action between the O and Si atoms despite silicon’s high affinity for oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In our laboratory the title compound C 24 H 23 NO 2 Si (I) was isolated as an intermediate in the synthesis of the respective sila amine. It is a congener of 2-(((4-methoxyphenyl)dimethylsilyl)methyl)isoindoline-1,3-dione (Guzei et al, 2010a) and 2-(2-(trimethylsilyl)ethyl)isoindoline-1,3-dione (Guzei et al, 2010b) recently reported by us. These sila amines were subsequently coupled with a selection of pharmaceutical agents containing a carboxylic acid, including indomethacin and N-acetyl L-cysteine (Zakai et al, 2010) as part of our continuing efforts at drug repurposing (Gately & West, 2007) using silicon chemistry (Bains & Tacke, 2003).…”
Section: S1 Commentmentioning
confidence: 91%
“…In our laboratory the title compound C 24 H 23 NO 2 Si (I) was isolated as an intermediate in the synthesis of the respective sila amine. It is a congener of 2-(((4-methoxyphenyl)dimethylsilyl)methyl)isoindoline-1,3-dione (Guzei et al, 2010a) and 2-(2-(trimethylsilyl)ethyl)isoindoline-1,3-dione (Guzei et al, 2010b) recently reported by us. These sila amines were subsequently coupled with a selection of pharmaceutical agents containing a carboxylic acid, including indomethacin and N-acetyl L-cysteine (Zakai et al, 2010) as part of our continuing efforts at drug repurposing (Gately & West, 2007) using silicon chemistry (Bains & Tacke, 2003).…”
Section: S1 Commentmentioning
confidence: 91%
“…We conclude that the instrument hardware is robust and well suited for routine crystallographic characterization of both stable organic and organometallic compounds. Six articles based on the data acquired have been published in the crystallographic journal Acta Crystallographica E , which rigorously checks crystal data and structure quality.…”
Section: Resultsmentioning
confidence: 99%
“…This system has been successfully tested at the American Crystallographic Association 2009 summer school and sold to at least three chemistry sites in the United States. The informal reviews were good and several articles containing structural results based on SMART X2S data have been published by others and by us .…”
Section: Testing the Instrumentmentioning
confidence: 95%